Identificação do sofrimento mental em estudantes do curso técnico em Enfermagem - Barcelos, Andrya Barbosa (2020)
Introduction: Entering a course in the student context means a new moment of experiences in the students' lives and may bring with it fear, insecurity, new responsibilities, thus facilitating the appearance of Common Mental Disorder. There are several instruments for identifying these disorders, one of the main ones being the Self Reporting Questionnaire-20, which is a low-cost and highly successful instrument in research. Objective: To identify the socioeconomic profile of students in the technical nursing course and to relate it to mental suffering. Method: This is a descriptive, prospective study with a quantitative approach that was conducted during the period from May to October 2019, with 54 students of the technical nursing course of a public educational institution. For data collection, the socioeconomic questionnaire and the Self Reporting Questionnaire-20 instrument were used. The data obtained were analyzed using the Microsoft Excel® Program and the Sigma Stat® 2.03 Statistical Program. Results: the data found were able to predict the relationship between mental suffering and the variables of the course, having children, age and sex. Indicating that being at the end of the course reduces the chances of suffering by 83% (OR = 0.17); having children decreases by 76% (OR = 0.24), and as age increases by one year, the chances of suffering drop by 8% (OR = 0.92), just as mental suffering was greater in women. Conclusion: the students with mental suffering are mostly young, female, enrolled in the initial period of the technical course, without children or religion, demonstrating that there is a relationship between certain variables of the socioeconomic data and mental suffering, which may favor the appearance of Common Mental Disorder.